86. Biological effects evaluation in peripheral blood lymphocytes from patients undergoing radium-223 (223RaCl2) therapy. (December 2018) - Dini, V.; Testa, A.; Patrono, C.; Balduzzi, M.; Palma, V.; Sciuto, R.; Soriani, A.; Strigari, L.; Marconi, R.; Tabocchini, M.A.
Abstract : Purpose: The purpose of this study is to correlate the physical dose to non-target tissues (blood) to the radiation-induced chromosome damage in terms of the dicentrics and micronuclei (MN) in peripheral blood lymphocytes (PBL) after radium-223 (223RaCl2) therapy in patients with bone metastasis derived from prostate cancer[1] . Methods: Four patients undergoing 223RaCl2 therapy for skeletal diseases have been enrolled in this prospective clinical study. The effective dose to blood per injected activity was calculated considering the alpha, beta and gamma emission of Ra-223 and considering a standard man weight of 70 kg. PBL cultures for dicentric assay and MN were performed before treatment (T0), 6 days (T1) and 30 days (T2) after the first cycle of treatment and after the end of the therapy (T3). Haematological toxicity parameters (blood cell count) have been monitored during therapy and analysed along with doses to blood. Results: The administration of 223RaCl2 produces a high dose dependent increase of radiation-induced chromosome damage in terms of dicentrics and MN induction observed in the circulating lymphocytes. Surprisingly, the increase of chromosome damage observed between T1 and T2 is not due to an 223RaCl2 addition dose, suggesting that circulating lymphocytes were exposed to an extra dose by the emissions from the target areas. In addition, clinical monitoring during the treatment showed a progressive increasing fatigue, leucopenia and anemia with a partial recovery after some months after the end of therapy. Conclusions: The cytogenetic data suggest a persistence of the radiation emission from the target tissue to non-target ones and seem to be correlated to the observed haematological toxicity, highlighting possible adverse effects related to this therapy. These data need further investigation in order to evaluate the potential side effects to normal, non-target tissue in patients treated with alpha emitters.